2013
DOI: 10.1016/s2213-2600(13)70105-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-acid treatment and disease progression in idiopathic pulmonary fibrosis: an analysis of data from three randomised controlled trials

Abstract: Background Abnormal acid gastroesophageal reflux is common in idiopathic pulmonary fibrosis and is considered a risk factor for its development. Retrospective studies have suggested improved outcomes in patients treated with anti-acid therapy. The aim of this study was to determine the association between anti-acid therapy and disease progression in idiopathic pulmonary fibrosis. Methods Patients with IPF were identified from the placebo arms of the three IPFnet randomized clinical trials. Case report forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
274
2
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(301 citation statements)
references
References 38 publications
3
274
2
22
Order By: Relevance
“…There was no significant difference between esophageal dilation and the grade of esophagitis by covariance analysis (Table s 3 and 4). pime pime pime pime p pi im me e EDITRICE Original Article pose the patient to the recurrent microaspiration and different respiratory complications including lung abscess, asthma and interstitial lung disease (ILD) [1,[20][21][22][23]. Secondly, ED might be correlated with the severity of lung disease or may be a clue for diagnosis of a serious underlying disorder.…”
Section: Radiologic Measurementmentioning
confidence: 99%
“…There was no significant difference between esophageal dilation and the grade of esophagitis by covariance analysis (Table s 3 and 4). pime pime pime pime p pi im me e EDITRICE Original Article pose the patient to the recurrent microaspiration and different respiratory complications including lung abscess, asthma and interstitial lung disease (ILD) [1,[20][21][22][23]. Secondly, ED might be correlated with the severity of lung disease or may be a clue for diagnosis of a serious underlying disorder.…”
Section: Radiologic Measurementmentioning
confidence: 99%
“…40 A retrospective analysis of the placebo arm of three IPF RCTs which compared patients on acid suppression with those who were not, found that the use of anti-acid therapy was associated with a slower decline in FVC over time and fewer acute exacerbations. 41 Interestingly, research studies have also shown that gastric contents that are not acidic are also capable of causing cellular injury in the lung. 40,41 To address the issue of reflux worsening disease, a clinical trial is currently being undertaken in the US comparing decline in FVC in IPF patients who have undergone fundoplication to those who have not (clinical trial number NCT01982968).…”
Section: Anti-acid Therapymentioning
confidence: 99%
“…41 Interestingly, research studies have also shown that gastric contents that are not acidic are also capable of causing cellular injury in the lung. 40,41 To address the issue of reflux worsening disease, a clinical trial is currently being undertaken in the US comparing decline in FVC in IPF patients who have undergone fundoplication to those who have not (clinical trial number NCT01982968). The recent ATS guidelines conditionally recommend empirical treatment of gastro-oesophageal reflux in IPF patients but acknowledge that good-quality evidence is currently lacking.…”
Section: Anti-acid Therapymentioning
confidence: 99%
“…It is known that IPF patients have significantly worse gastrooesophageal reflux than controls, and pepsin originating from the gastrointestinal tract has been isolated in BAL fluid in patients with acute exacerbations of IPF (4,26). Interestingly, the use of anti-acid therapy has been associated with a slower decline in FVC over time and fewer acute exacerbations (27). Current guidelines recommend empirical treatment of gastro-oesophageal reflux in IPF patients, but good quality evidence is lacking (3,4).…”
Section: Anti-acid Therapymentioning
confidence: 99%